Serum Hormones and Anticonvulsants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Circulating sex and thyroid hormones were assessed in 63 male young adults with epilepsy in the Departments of Neurology and Clinical Chemistry, University of Oulu, Finland.